PENGARUH TERPAAN INFORMASI KESEHATAN WAJAH DI TIKTOK TERHADAP KEPUTUSAN PEMBELIAN PRODUK SUNSCREEN OLEH FOLLOWERS @DR.ZIEE - Rifqah Ramadhani Akbar (2023)
Women are often faced with the mistakes of improper sunscreen application or a lack of understanding about the importance of using sunscreen regularly and in sufficient amounts. This can reduce the effectiveness of skin protection from the dangers of sunlight and increase the risk of exposure to harmful UV rays. This study aims to investigate the influence of facial health information exposure on the TikTok social media platform on sunscreen product purchasing decisions. The research will employ a quantitative research method with a survey approach, using a descriptive research type, and applying the Elaboration Likelihood theory to determine the extent of TikTok social media information exposure on the @dr.ziee account's impact on sunscreen product purchasing decisions. A total of 100 respondents who are followers of the TikTok account @dr.ziee will be the subjects of this study. Based on the correlation test results, a correlation coefficient of 0.609 is obtained, indicating a strong relationship between variable X and variable Y. The coefficient of determination test results show that the level of influence of variable X on variable Y is 38.7%, indicating that variable X has a significant influence on consumer buying interest. The regression coefficient is 0.881 (positive). Through the hypothesis test results, the calculated t-value of 7.859 > t-table 1.984, indicating that the alternative hypothesis (Ha) is accepted, which states that there is a significant and large influence of variable X on variable Y.